Basic Needs and Self-Actualization of Baek Kang-Hyeok in the Korean Drama The Trauma Code: Heroes on Call - Lailatun Nadifah; Fafi Inayatillah (Raja Zulkarnain Education Foundation, 2026)
The purpose of this study is to analyze Baek Kang-Hyeok's basic needs and self-actualization needs, as well as to motivate the surrounding community when fulfilling these needs, from the most basic to the fulfillment of self-actualization needs. Basic needs are indicated by physiological needs, safety needs, belonging needs, and esteem needs. Furthermore, higher needs are the self-actualization needs of Baek Kang-Hyeok in the Korean drama